You are on page 1of 2

28.

(a) We can rewrite the transform as:

1 s −a+ s +a 1æ 1
s 1 ö
fˆ (s ) = = çç + =
÷÷ Þ
( )(
s −a s +a 2 s −a s +a 2è s +a )
s −aø ( )( )
1 æç 1 1 ö
fˆ (s ) = + ÷ (1)
2 s çè 1 + a s 1 − a s ÷ø

Now, for s → ∞ , we have a s → 0 and we can use the geometric series:

1 a2 a3
a a4 a5 æ1ö
= 1+ + + + 2 + 2 + Oç 3 ÷ (2)
1− a s s s s s s s s ès ø
1 a a2 a3 a4 a5 æ1ö
= 1− + − + 2 − 2 + Oç 3 ÷ (3)
1+ a s s s s s s s s ès ø

Thus the transform can be written as:

ˆf (s ) = 1 é2 + 2 a + 2 a + Oæç 1 ö÷ ù = 1 + a + a + Oæç 1
2 4 2 4
ö
ê 3 ú ç 3 ÷÷ (4)
2 së s s2 è s øû s s s s2 s ès sø

Taking the inverse transform we get, for t > 0 :

f (t ) =
1
πt
+ 2a 2 t 4a 4
π
+
3
t
t
π
+ O t2 t ( ) (5)

In order to compare this with the analytical solution, we need the Taylor series of:

( )
a t a t

ò [1 − τ ( )]
2 2 2 2 2 2

ò e dτ =
−τ
ae a t erf a t = ae a t ae a t 2
+ O τ 4 dτ =
π 0 π 0

=
2a
[1 + a t + O(t )]éêa
2 a 3t t 3
ù
+ O t2 t ú = t− ( ) (6)
π ë 3 û

=
2a é
ê
π ë
2
a t + a 3t t + O t 2 t ú
3
ù
( )
û

Thus the expansion about t = 0 of the analytical solution is:

f (t ) =
1
πt
2
+ ae a t erf a t = ( ) 1
πt
+ 2a 2
t 4a 4
π
+
3
t
t
π
+O t2 t ( ) (7)

This coincides with (5).

(b) We can rewrite the transform as:

2a
fˆ (s ) = 1 + −1 (8)
s

As s → ∞ , we have 2a s → 0 . The Taylor series expansion of 1 + x about x = 0 is:

1 1 1
1+ x = 1+
2
x − x2 + x3 + O x4
8 16
( ) (9)

Thus we have:

2a 1 2a 1 4a 2 1 8a 3 æ 1ö a a
2
a3 æ 1ö
fˆ (s ) = 1 + −1 = − 2
+ 3
+ O ç 4 ÷ = − 2
+ 3
+ Oç 4 ÷ (10)
s 2 s 8 s 16 s è s ø s 2s 2s ès ø

Taking the inverse transform we obtain:

a2 a3
f (t ) = a − t + t 2 + O(t 3 ) (11)
2 4

f (t ) = a exp(− at )[I1 (at ) + I 0 (at )] Þ

é a2 2 3 ù é at a 3t 3 a 2t 2 ù
Þ f (t ) = a ê1 − at +
2
t + O t úê +( ) ( )5
+ O t +1+ ( )
+ O t4 ú Þ
ë ûë 2 16 4 û
é æa ö æa
2 2
a ö
2
ù 2 3
÷÷t + O(t 3 )ú = a − t + t 2 + O(t 3 )
a a a
Þ f (t ) = a ê1 + ç − a ÷t + çç − + (12)
ë è2 ø è 4 2 2 ø û 2 4